Pengaruh Kualitas Produk dan Pemasaran Digital Terhadap Niat Beli Ulang dengan Kepuasan Sebagai Variabel Mediasi: Studi pada Pelanggan UMKM Batik Dahon - Pya Agustian; Endang Tjahjaningsih (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine and analyze the influence of product quality and digital marketing on repurchase intention through customer satisfaction at the Batik Dahon . The research method implemented in this study is explanatory research with a quantitative approach. The population in this study was 351 Batik Dahon MSME consumers in October 2025, with a sample size of 100 respondents. The data collection instrument used a questionnaire with a Likert scale that has been tested for validity and reliability. The data analysis techniques used were multiple regression analysis and the Sobel test to examine the direct and indirect (mediation) effects between variables. The results show that: (1) Product quality has a direct positive effect on customer satisfaction; (2) Digital marketing has a direct positive effect on customer satisfaction; (3) Product quality has a direct positive effect on repurchase intention. (4) Digital marketing has a direct positive influence on repurchase intention; (5) Customer satisfaction does not significantly influence repurchase intention; (6) Customer satisfaction mediates the influence of product quality on repurchase intention; and (7) Customer satisfaction does not mediate the influence of digital marketing on repurchase intention at the UMKM Batik Dahon